Outcomes After Selective Fasciotomy for Revascularization of Nontraumatic Acute Lower Limb Ischemia. (January 2022) - Lin, Jonathan H.; Humphries, Misty D.; Hasegawa, Jason; Saroya, Jasmeet; Mell, Matthew W.
Objectives: Limited data support the use of fasciotomies in acute limb ischemia (ALI) in patients with isolated arterial occlusion. This study describes an experience in which fasciotomies are not regularly performed post-revascularization.Methods: Using International Classification of Diseases, Ninth and Tenth Edition codes, patients presenting to the University of California Davis Medical Center between January 2003 and July 2018 with ALI, excluding those with traumatic injuries were identified. The primary outcome was major amputation, and the secondary outcome was foot drop. Additionally, the characteristics of those patients in each category of ischemic severity excluding those with grade 3 ischemia were summarized.Results: Of the 253 patients identified, revascularization was successful in 230 patients with 11 total fasciotomies performed. One hundred thirty-five patients were Rutherford Class 1/2A and 95 were 2B. In those with 1/2A ischemia, 134 (102 had >6 hours of symptoms) did not undergo fasciotomy with only one amputation occurring in this group. In those with 2B ischemia, 65 had >6 hours of symptoms; 58 did not undergo fasciotomy with 4 major amputations. In the 30 patients with ≤6 hours of ischemic symptoms, 27 did not undergo fasciotomy with 1 major amputation occurring in this group. There were no amputations in those patients who underwent fasciotomies. Additionally, there were 14 patients with a foot drop, of which 11 were in patients with 2B ischemia without fasciotomy.Conclusions: The data suggest that regardless of ischemic duration, 1/2A patients may not need fasciotomies, while those patients with 2B ischemia may benefit.